Injury risk in professional football players with special reference to the playing position and training periodization - Mallo, J.; Dellal, A (The Journal of Sports Medicine and Physical Fitness, 2012)
Aim: The aim of this study was to examine injury incidence in professional football players according to the playing positions and with a special reference to training periodization. Methods: A Spanish professional team was followed prospectively for the 2007-08 and 2008-09 seasons and exposure times and time-loss injuries were individually recorded during all training sessions and matches. Heart rate was monitored in all training sessions. Results: Total of 114 injuries were registered during the study period (mean injury incidence: 6.6 injuries per 1000 hours). The frequency of injuries was not uniformly distributed by playing positions (P<0.001), as forwards and central defenders sustained the greatest number of injury episodes and the highest match absence. Ligament sprains and muscle strains accounted for 50% of all injuries and 62% of all match absences. The highest incidence of sprains was achieved during pre-season and the beginning of the competition period. The risk to sustain a muscular strain peaked at the beginning and in the final weeks of the competition period and was related (r=0.72; P<0.05) to mean heart rate during the training stage. Conclusion: The results suggest that there exists a difference of injury risk according to the period of the season and therefore, injury prevention strategies should be introduced from pre-season. Moreover, training workloads should be controlled to avoid increasing the risk of muscle strains.